s-3t=rt

Simple and best practice solution for s-3t=rt equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s-3t=rt equation:


Simplifying
s + -3t = rt

Solving
s + -3t = rt

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '3t' to each side of the equation.
s + -3t + 3t = rt + 3t

Combine like terms: -3t + 3t = 0
s + 0 = rt + 3t
s = rt + 3t

Simplifying
s = rt + 3t

See similar equations:

| A/3-=2 | | t=(t+20)+(t+10) | | -5(1-5x)+5(-8x-2)=-5x-45 | | t=(t+10)+(t+20) | | 65(3h)+130=h | | 5-2(7x+2)= | | 8+5x=9x-8 | | 8+5x=8x-8 | | 6p+10=360 | | 24x-22=-4(1-6k) | | A=9/8(h-75) | | (3+7i)+(4+5i)=0 | | 6x+10=360 | | 0.142857= | | x^2-6x+16=7 | | 7j-10=60 | | (2x-8)^2/3 | | 3(y-5)/4-4y=3(y-3)/2 | | -x+14=-5x+6 | | -7x+16=-3x-16 | | 11x-5=4x+37 | | 4x+19=-2x+61 | | -24=8-(8*r) | | -4x+19=47 | | -4x+11=19 | | -24=8-8r | | 9x+11=2x+74 | | 3a+4b-a-2b= | | f(2)-f(5)=8x-12 | | 4y-x+8=0findy | | 11(2b-1)-(3b-7)=1 | | 5(x-2)=7x-16 |

Equations solver categories